Modele równań strukturalnych z wykorzystaniem środowiska R - Sztemberg-Lewandowska, Mirosława (Structural Equation Models with R, 2009)
Structural Equation Models (SEM) are multi-equation regression models. These structural equations are meant to represent causal relationship among the variables in the model. Structural equation modeling is a very general, powerful multivariate analysis technique that includes the specialized versions of a number of other analysis methods as special cases. Factor analysis, path analysis and regression represent special cases of SEM. In this article, the author presents packages and functions in R system, which computed SEM. The aim of the article is o characterize these functions and illustrate them with the use of empirical examples. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 180-188